The Archaeology, Ethnohistory, and Coastal Environment of the Marismas Nacionales : the Prehistoric Pacific Littoral of Sinaloa and Nayarit, Mexico - Foster, Michael S. (Michael Stewart), 1947- (The University of Utah Press, 2017)
"The first consolidated analysis of the only large-scale archaeological research project ever undertaken in the Marismas Nacionales on the northwest coast of Mexico. Between 1967 and 1975 archaeologists from SUNY-Buffalo led a multidisciplinary project in the Marismas Nacionales, a vast, resource-rich estuary and mangrove forest of coastal Sinaloa and Nayarit, west Mexico. Michael Foster and fellow archaeologists provide a much-needed synthesis of these investigations, drawing from previously unpublished data and published reports to provide a comprehensive look at the region. While in the field, the SUNY team recovered a variety of material artifacts and the remains of 248 humans. Their findings, along with the project's background, history, and analyses, are detailed in this volume's thirteen chapters and eleven appendices. Also included are supporting geomorphic, environmental, and ethnohistoric studies that establish the context for local human settlement and change. Among the discoveries, evidence indicates that as the coastal plain grew, ceramic-bearing agriculturalists moved into the area and participated in far-reaching exchanges of goods and resources. This book makes a significant and lasting contribution to our knowledge of what today remains an understudied region of greater Mesoamerica"--Provided by publisher.